Factors impacting self-pay pediatric vaccine utilization in China: a large-scale maternal survey. Issue 8 (August 2020) - Li, Xinxin; Lu, Haiyan; Wu, Han; Chen, Qiuhua; Wu, Ping; Pan, Qingjun
Objectives: Utilization of self-pay vaccines worldwide is very low, especially in China; the reasons for this are unclear. We aimed to identify factors that impact the decision among Chinese mothers to utilize self-pay vaccines for their children. Methods: Mothers who were hospitalized at two hospitals in Zhanjiang City and who agreed to participate by completing the required questionnaire were eligible for this study. Results: In total, 7518 respondents (n = 7592) completed the questionnaire and were included in this survey. The self-pay option was largely elected by mothers with one child, compared with those who had two or more children. Similarly, utilization by workers at government agencies and organizations was higher than that among factory workers or unemployed respondents. Mothers with a college degree or above had higher utilization than those with a high school level education or lower. The main issues affecting maternal decisions to utilize self-pay pediatric vaccines were safety, the protective effect, and the high cost. Conclusion: Mothers with higher socioeconomic status were more inclined to self-pay for pediatric vaccines. Steps taken to enhance public awareness about the safety and protective benefits of self-pay vaccines, as well as lowering their cost will likely encourage broader utilization of these vaccines.